Study of the Expression of Helicobacter Pylori Urei Gene by RT-PCR - M Fazeli; A Doosti (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2017)
BACKGROUND AND OBJECTIVE: Helicobacter pylori is a spiral shaped and gram negative bacterium which causes peptic ulcer and has an important role in gastric carcinoma. Different components of urease are the important factor to stimulate the immune system. There is no effective vaccine against this bacteria and research on finding an effective vaccine is necessary. The aim of present study was to produce ureI gene construct and evaluation of the expression of this gene. METHODS: In this experimental study, the amplification of ureI gene was performed using PCR on standard strains of H. pylori genome that obtained from Pasteur institute. 612 bp fragment of ureI gene was cloned by T/A cloning technique into pTZ plasmid, and sub-cloning was done in PIRES2-EGFP vector. PIRES2-EGFP-ureI recombinant vector was transformed using electroporation into CHO cells and ureI gene expression was evaluated by RT-PCR. FINDINGS: Cloning of 612 bp fragment for ureI gene in pTZ and PIRES2-EGFP vectors had confirmed using PCR, digestion by SacI/EcoRI restriction enzymes and sequencing. After the RT-PCR on transformed CHO cells, the ureI gene fragment was observed. CONCLUSION: The PIRES2-EGFP-ureI recombinant vector can express the ureI gene. The successful gene expression of this target gene in animal cells can be used to evaluate the immunogenicity as a vaccine in laboratory animals. Also, this generated recombinant vector has the potential for assay as DNA vaccine in future experiments